The nitrate transporter OsNPF7.9 mediates nitrate allocation and the divergent nitrate use efficiency between indica and japonica rice. Issue 1 (11th February 2022) - Guan, Yuan; Liu, De-Fen; Qiu, Jie; Liu, Zhi-Jun; He, Ya-Ni; Fang, Zi-Jun; Huang, Xue-Hui; Gong, Ji-Ming
Abstract: Nitrate allocation in Arabidopsis ( Arabidopsis thaliana ) represents an important mechanism for mediating plant environmental adaptation. However, whether this mechanism occurs or has any physiological/agronomic importance in the ammoniphilic plant rice ( Oriza sativa L.) remains unknown. Here, we address this question through functional characterization of the Nitrate transporter 1/Peptide transporter Family (NPF) transporter gene OsNPF7.9 . Ectopic expression of OsNPF7.9 in Xenopus oocytes revealed that the gene encodes a low-affinity nitrate transporter. Histochemical and in-situ hybridization assays showed that OsNPF7.9 expresses preferentially in xylem parenchyma cells of vasculature tissues. Transient expression assays indicated that OsNPF7.9 localizes to the plasma membrane. Nitrate allocation from roots to shoots was essentially decreased in osnpf7.9 mutants. Biomass, grain yield, and nitrogen use efficiency (NUE) decreased in the mutant dependent on nitrate availability. Further analysis demonstrated that nitrate allocation mediated by OsNPF7.9 is essential for balancing rice growth and stress tolerance. Moreover, our research identified an indica–japonica divergent single-nucleotide polymorphism occurring in the coding region of OsNPF7.9, which correlates with enhanced nitrate allocation to shoots of indica rice, revealing that divergent nitrate allocation might represent an important component contributing to the divergent NUE between indica and japonica subspecies and was likely selected as a favorable trait during rice breeding. Abstract : Nitrate allocation between roots and shoots contributes to the divergent nitrogen use efficiency between indica and japonica subspecies.